1956
DOI: 10.1111/j.1469-185x.1956.tb01555.x
|View full text |Cite
|
Sign up to set email alerts
|

THE TRANSPORT OF CALCIUM and OTHER CATIONS IN SUBMERGED AQUATIC PLANTS

Abstract: SUMMARY Photosynthetic bicarbonate assimilation and cation transport by aquatic plants are reviewed. It is suggested that these two processes stand in a causal relation to one another. A number of observations of cation transport not directly associated with photosynthesis are also reviewed, and are related to current concepts of active transport in the plant kingdom. These characteristics of cation transport have been observed in many submerged aquatic plants: Cations are transported through the leaves in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1958
1958
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Reductions in ambient cation levels have been demonstrated in the microhabitat beneath some photosynthetically active hydrophytes (Lowenhaupt 1956, Prins et al 1982c. Reductions in ambient cation levels have been demonstrated in the microhabitat beneath some photosynthetically active hydrophytes (Lowenhaupt 1956, Prins et al 1982c.…”
Section: Identification Of the Settling Factormentioning
confidence: 97%
“…Reductions in ambient cation levels have been demonstrated in the microhabitat beneath some photosynthetically active hydrophytes (Lowenhaupt 1956, Prins et al 1982c. Reductions in ambient cation levels have been demonstrated in the microhabitat beneath some photosynthetically active hydrophytes (Lowenhaupt 1956, Prins et al 1982c.…”
Section: Identification Of the Settling Factormentioning
confidence: 97%
“…The excretion of OH -ions from the adaxial leaf surfaces is accompanied by cations (e .g . Lowenhaupt, 1956 ;Raven, 1971) . Although there are few detailed reports of other divalent cations being excreted along with Ca 2 + and OH -in Potamogeton spp .…”
Section: Modern Sedimentsmentioning
confidence: 99%
“…Experiments on various species of submerged macrophytes (Lowenhaupt, 1956 ;Steeman Nielsen, 1951) have shown shoots are the main organs of nutrient absorption and that roots act mainly as anchors (Olsen, 1953Sutcliffe, 1962 . Spence (1967) concluded that both hypotheses may be partly correct .…”
Section: Concentrations Of Investigated Metals and As Inmentioning
confidence: 99%